STRUCTURAL EQUATION MODELLING ANALYSIS DETERMINING MOTIVES FOR LOW SOCIAL STATUS JOBS IN BOJONEGORO - Vellyana, Salsa Devi; Susilo, Joko Hadi; Endang, Endang (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The purpose of this study was to determine the influence of low social status, age, family economic conditions, on the motives of working as beggars in Bojonegoro through education level as an intervening variable. The method used in this study is a descriptive quantitative method with a parametric Structural Equation Modeling approach to measure direct and indirect relationships in each variable. The population in this study were beggars in Bojonegoro Regency. The number of respondents in this study was 30 beggars in Bojonegoro Regency. The results of this study found low social status significant to motive for working as a beggar. Low social status not significant to education level. Age not significant to motive for working as a beggar. Age significant to education level. Family economics condition not significant to motive for working as a beggar. Family economics condition significant to education level. This study confirms that the social environment has an important role in a person's life. A person's bad behavior depends on the values adopted in their social environment.